IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA MELALUI PROGRAM KULIAH KERJA NYATA DI DUSUN SAMBUNG LOR DESA JAMBEWANGI KECAMATAN SECANG TAHUN 2024 - Siti Musyarofah; Muhammad Mas'ud; Andika Bayu Saputra; Izzatunnisa Azzahra; Fahru Nisa (ALKADIMAT, 2024)
Secang is one of the sub-districts in Magelang Regency, which is located in the north of Pringsurat District, Temanggung Regency, in the east of Grabag District, in the south of North Magelang District, Magelang city, and in the west of Windusari District. Secang District is one of the places that has often been used as a location for KKN by various higher education institusiions, one of which is UIN Salatiga. UIN Salatiga carries out KKN programs using the theme of religious moderation. Religious moderation is carrying out the teachings that have been learned from the religion they profess in a non-excessive or extreme manner. The purpose of this KKN is that students can practice the knowledge they have learned on campus by going directly into the community and living side by side moderately. The community service method of KKN Religious Moderation uses the type of PAR Participatory Action Research or community participation action research in Sambung Lor Hamlet. The results of the Religious Moderation KKN activities show that religious moderation in the surrounding community is good enough so that students can easily convey some of the knowledge gained from campus. The response from the surrounding community was also very good in receiving participants of the Religious Moderation KKN. The community of Sambung Lor Hamlet also participated in activities carried out by participants of the Religious Moderation KKN. Thus, the work program of the Religious Moderation KKN in Sambung Lor Hamlet can run smoothly because of the support from all surrounding communities and various parties who have been involved in the running of this Religious Moderation KKN program activity.